Higher plasma motilin levels in obese patients decrease after Roux-en-Y gastric bypass surgery and regulate hunger. Issue 7 (18th May 2015) - Deloose, E; Janssen, P; Lannoo, M; Van der Schueren, B; Depoortere, I; Tack, J
Abstract : Objective: Motilin-induced phase III contractions of the migrating motor complex (MMC) signal hunger in healthy volunteers. The current aim was to study the role of motilin as a hunger-inducing factor in obese patients and to evaluate the effect of Roux-en-Y gastric bypass (RYGB) surgery on plasma motilin levels and hunger scores. Design: Motilin and ghrelin plasma levels were determined during a complete MMC cycle in controls and obese patients selected for RYGB before, 6 months and 1 year after surgery. 20 min after the end of the second phase III, obese patients received an intravenous infusion of 40 mg erythromycin. Hunger was scored every 5 min. Hedonic hunger was assessed in obese patients with the Power of Food Scale questionnaire. Results: Obesity caused a switch in the origin of phase III from antrum to duodenum. Obese patients had significantly higher motilin levels compared with controls during the MMC but tended to lack the motilin peak prior to phase III necessary to trigger hunger. Hunger scores during phase III were significantly lower in obese patients, but could be restored to control levels through the administration of a low dose of the motilin agonist, erythromycin. After RYGB surgery motilin, but not ghrelin, levels decreased in parallel with hedonic hunger scores. Conclusions: Motilin may be an important regulator involved in the pathogenesis of obesity.